Financial contagion during global financial crisis and covid-19 pandemic: The evidence from DCC-GARCH model - Thi Ngan Nguyen; Phan Thi Kieu Hoa; Nguyen Thanh Liem (Cogent Economics & Finance, 2022)
This paper is the first study to examine the financial contagion from the U.S., Japanese and Chinese markets to Asian markets during the Global Financial Crisis (GFC) and Covid-19 Pandemic Crisis. We employ the DCC-EGARCH methodology and daily data of stock returns from 2005 to 2021 to estimate the time-varying correlations and the volatilities of stock markets. Our results show that the correlation between the U.S. and Japanese markets with emerging Asian ones is quite high, implying the interdependence between these markets. Furthermore, we find significant contagion effects from the U.S. equity market to markets in both advanced and emerging economies during the GFC. Nonetheless, during the Covid-19 pandemic, only 3 out of 10 Asian emerging markets had experienced the contagion from the U.S. Our findings also suggest that contagion effects are not strongly related to the level of global integration and Asian markets seem to be more affected by the contagion from Japan and China.
Keywords: 330; Contagion; COVID-19 Pandemic; DCC - EGARCH model; Global Financial Crisis; stock marke